Technology Roadmap: Nanomaterials Applied to the Tertiary Treatment of Industrial Wastewater Contaminated by Synthetic Organic Dyes - Livia G. Monteiro; Marco A.G. Figueiredo (Chemical engineering transactions, 2023)
Industrial wastewater contaminated by synthetic organic dyes is a major environmental threat that needs treatment for its adequacy and, consequently, minimization of pollution of terrestrial water resources during its reintroduction into receiving water bodies. In recent decades, advances in nanotechnology have contributed to this path, allowing the application of nanomaterials (NMs) designed in different treatment techniques. Thus, the objective of this work includes the verification of trends related to the application of NMs to the tertiary treatment of industrial wastewater contaminated by synthetic organic dyes, using the Technology Roadmapping (TRM) method. Scientific articles and patent documents on the subject were extracted from the WIPO PatentScope, PatentInspiration, INPI and Scopus databases, with a total of 215 scientific articles, 27 granted patents and 52 requested patents considered relevant and analyzed. Through this study, it was possible to identify the main countries and universities in terms of technical-scientific production, such as China, India and Saudi Arabia, represented by the Chinese Academy of Sciences, Amity University and King Abdulaziz University. In the short, medium and long term, there is a tendency towards diversification of raw materials, with studies focusing on the use of mineral, synthetic, biological and residual inputs. In addition, there is also a propensity to search for hybrid and multifunctional NMs, to overcome the existing difficulties in their independent forms, impressively meeting market expectations.